Македонські шопи – кордони, ідентичність і перспективи - Малинов, З. (Народна творчість та етнографія, 2009)
The Shops that live in the Republic of Macedonia settle the north-eastern part of its territory, which is extended to the territory the Shops (so called Shopluk) of the neighboring countries of Bulgaria and Serbia. However, with the exception of some regions (i.e. parts of the districts of Kriva Palanka and Kratovo), almost all members of this ethnographic group avoid this ethnonym and from a ethnoregional aspect they prefer to identify themselves as Maleshevtsi, Piyanchani, Ossogovtsi etc. The differences of the dialects, costumes, traditional way production, mentality and alike contribute to this identification too. The integral text of my contribution will offer more information in relation to this very specific south Slavic ethnic group spread on the borders of the above-mentioned three states from a historical and ethnological aspect, but also from the their own perspective of United Balkans within United Europe.